Navigasi Robot Beroda menggunakan Algoritma SVM (Support Vector Mechines) - Nengah Affan Riadi; Gembong Edhi Setyawan; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Wheeled robots need a navigation ability to operate properly. One of the navigation implementations of the wheeled robot is that the wheeled robot can help the SAR (Search and Rescue) team find victims. Wheeled robots need a navigation algorithm to do the job. This research will use one type of navigation algorithm, the SVM (Support Vector Machines) algorithm. In addition, the wheeled robot also requires a sensor and actuator that can support the performance of the wheeled robot. This research will use an Ultrasonic Sensor which is used to detect obstacles around the robot wheel and DC motor as the propulsion of the wheeled robot. The results of the tests conducted in this study, obtained the best PWM (Pulse Width Mudulation) motor value that will be used for operating robots is 150, Ultrasonic Sensors and DC Motors have a pretty good functionality and can be used in robots with wheels well, and accuracy SVM algorithm output that compares with the actual output is 87.5%.